Does Yearly Made Testing of Knowledge at Work Place Enhance Medical Personnel’s Self – Directed Learning in Their Lifelong Learning? - Dambe, Gundega; Atstāja, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of this paper is to clarify – whether yearly made testing of knowledge at a work place enhance NMP medical personnel’s self-directed and self-motivated lifelong learning and how it affects the results of work. The results of the research show, that the knowledge testing enhances personnel’s self-directed learning, however, it does not affect the results of work significantly. By analyzing the data of the survey on personnel’s attitude to the testing of knowledge data, the conclusion has been made that other factors of personnel’s motivation for lifelong learning have to be found.